2007
DOI: 10.1016/j.jacc.2007.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Platelet Reactivity After Clopidogrel Administration on Drug-Eluting Stent Thrombosis

Abstract: Nonresponsiveness to clopidogrel is a strong independent predictor of stent thrombosis in patients receiving sirolimus- or paclitaxel-eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
391
4
17

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 616 publications
(424 citation statements)
references
References 33 publications
(25 reference statements)
12
391
4
17
Order By: Relevance
“…24 Our results support the view that STEMI was a significant independent predictor of stent thrombosis. 25 Our study has several potential limitations. First, 3 of the 4 trials included in this meta-analysis had a protocolmandated follow-up angiography.…”
Section: Discussionmentioning
confidence: 88%
“…24 Our results support the view that STEMI was a significant independent predictor of stent thrombosis. 25 Our study has several potential limitations. First, 3 of the 4 trials included in this meta-analysis had a protocolmandated follow-up angiography.…”
Section: Discussionmentioning
confidence: 88%
“…В литературе накапливается все больше доказательств того, что высокие значения остаточной реактивности тромбоцитов, определенные in vitro у пациентов, получающих ДАТ, сопровождается риском таких нежелательных явлений, как тромбоз стента и смерть от сердечно-сосудистых событий [12,13]. В исследовании RECLOSE [14] у лиц с лабора-торной резистентностью к проводимой ДАТ частота тромбоза стента оказалась значительно выше, чем у больных, чувствительных к АТ.…”
Section: Discussionunclassified
“…Despite its proven benefit, inhibition of platelet function by clopidogrel treatment is characterised by large interindividual variability. It has been shown that hyporesponsiveness of platelets to clopidogrel therapy is an independent strong predictor of stent thrombosis [2,3]. We report a case of simultaneous stent thrombosis in a patient with acute myocardial infarction who had an established clopidogrel hyporesponsiveness.…”
Section: Introductionmentioning
confidence: 87%